Identifying fiscal inflation - Ferre De Graeve; Virginia Queijo von Heideken (Sveriges Riksbank, 2013)
Fiscal theorists warn about the risk of future in.ation as a consequence of current fiscal imbalances in the US. Because actual in.ation remains historically low and data on inflation expectations do not corroborate such risks, warnings for fiscal inflation are often ignored in policy and academic circles. This paper shows that a canonical NK- DSGE model enables identifying an anticipated component of in.ation expectations that is closely related to fiscal policy. Estimation results suggest that fiscal inflation concerns have induced a 1.6%-points increase in long-run inflation since 2001. The model also rationalizes why data on in.ation expectations do not reveal such concerns outright.
Keywords: E31; E62; 330; Fiscal policy; inflation; news